Alternative strategies and new insights into immunology, health, and performance of dairy cattle - Silva, Thiago Henrique da (2021)
There are two critical phases in dairy animals\' life. Still in the young phase, calves usually pass through a turbulent moment when they are moved from the individual housing phase to a group housing system after weaning. Another critical moment in dairy cattle\'s life is the transition from a non-lactating pregnant state to a non-pregnant lactating state in mature cows. Numerous studies have identified the negative impact of these phases on the homeorretic and homeostatic mechanisms. Therefore, the objective of the first study was to evaluate the effect of supplementing an ultra-diluted product in the first 112 days after grouping of Holstein heifers on the incidence of diseases and performance. Also, its carryover impacts up to first lactation was evaluated. Although there was no improvement on performance during the supplementation period, a lower incidence of diarrhea was detected for animals consuming the ultra-diluted product. In addition, a lower culling rate was detected at the raising phase after supplementation. A study was also conducted herein to test the potential effect of an ultra-diluted product on polymorphonucleate leukocytes (PMNL) function and respiratory disease of Holstein calves after grouping. No changes were detected in PMNL function or scores for respiratory disease. Regarding the impact of the transition period on mature dairy cows, a trial was performed to evaluate the effect of injectable trace mineral supplementation (Se, Cu, Zn and Mn) at dry-off, close-up, and 35 days after calving on immunity, incidence of diseases, reproductive outcomes, milk production, and survivability of dairy cows undergoing the transition period in semi-arid environment. No effects of injectable trace minerals were detected in productive and reproductive performance; however, a lower incidence of metritis and stillbirths was detected for cows supplemented. Also, greater PMNL function was detected for supplement treated group. Finally, in view of the need to evaluate a new method with greater feasibility that could replace or reduce the redundancy of techniques currently used in immune system evaluation of early postpartum dairy cows, a study was conducted to evaluate the association of natural antibodies (NAb; IgM and IgG), total immunoglobulins (Ig; M and G), and PMNL function of dairy cows on day 3 after calving. A positive correlation was detected between NabIgM and IgM. In addition, IgM was positively associated with PMNL function of dairy cows.